English in the political communication in India - Стиранко Єлизавета Вікторівна (My University, 2023)
The use of English in India, especially in political discourse, has become a critical and fascinating topic of discussion and extensive research. This growing interest can be attributed to several factors, including the impact of globalization and India's interactions with the international community. As India assumes a more prominent role on the global stage, the role of English in fostering national unity and shaping the Indian identity has gained significance. Renowned scholars such as David Crystal and Braj Kachru have dedicated their efforts to studying the multifaceted role of English in India. Their work has shed light on the unique features of Indian English that distinguish it from standard English, highlighting its distinct vocabulary, syntax, and pronunciation. This research contributes to a deeper understanding of India as a country undergoing dynamic transformations, taking into account the lingering influences of its postcolonial legacy. By illuminating the linguistic dimensions of Indian political discourse, this thesis facilitates a more nuanced exploration of India's evolving identity and its complex relationship with the English language.
Keywords: English; political communication; India